Diffuse Large B Cell Lymphoma with Cutaneous and Gastrointestinal Involvement - Aye-Mya-Mya Kyaw; Than-Than Aye; Lin-Lin Htun (Case Reports in Gastrointestinal Medicine)
Diffuse large B cell lymphoma (DLBCL) is the histological subtype of non-Hodgkin’s lymphoma, representing approximately 30%. The most common primary extranodal sites of DLBCL are the gastrointestinal (GI) tract, the head and neck, and the skin/soft tissue. We report a case of DLBCL with cutaneous involvement presenting with skin nodules and GI manifestations such as obstructive jaundice and upper GI bleeding. Malignant cystic pancreatic tumor occupying the head and body with invasion to lower end of common bile duct and periampullary region causing biliary obstruction and mesenteric lymphadenopathy were found in abdominal computed tomography and endoscopic ultrasonography. There was also a large gastric ulcer (Forrest IIa) at the greater curvature of body of the stomach. Histopathological results of the skin and stomach were consistent with diffuse large B cell lymphoma; gastric biopsy being negative for leucocyte common antigen. The patient was considered to have disseminated DLBCL. The aim of the present case report was to present the clinical, radiological, and histological characteristics of the patient, which may aid physicians in diagnosing involvement of multiple extranodal sites in DLBCL.